2009
DOI: 10.1111/j.1096-3642.2008.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of Caribbean skinks of the genusMabuya(Reptilia, Scincidae), with descriptions of two new species from Venezuela

Abstract: Phylogenetic relationships among the species of Mabuya present around the Caribbean Sea (Antilles, Central America, and northern South America) are proposed for the first time. The molecular phylogenetic analyses (based on cytochrome b and 12S sequences) give new insights into the diversification of the genus in the New World, its multiple instances of montane habitat colonization, and the multiple waves of colonization towards the Caribbean area. In addition to the molecular analyses, we propose hypotheses ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The latter clade is weakly supported as the sister group to a clade containing Chioninia , Eumecia , and Mabuya . In Mabuya , a few species ( M. altamazonica , M. bistriata , and M. nigropuncata ) have unorthodox placements within a monophyletic Mabuya , potentially due to uncertain taxonomic assignment of specimens by previous authors [51,122]. The genus Lygosoma is paraphyletic with respect to Lepidothyris and Mochlus , and many of the relevant nodes are strongly supported (Figure 10).…”
Section: Resultsmentioning
confidence: 93%
“…The latter clade is weakly supported as the sister group to a clade containing Chioninia , Eumecia , and Mabuya . In Mabuya , a few species ( M. altamazonica , M. bistriata , and M. nigropuncata ) have unorthodox placements within a monophyletic Mabuya , potentially due to uncertain taxonomic assignment of specimens by previous authors [51,122]. The genus Lygosoma is paraphyletic with respect to Lepidothyris and Mochlus , and many of the relevant nodes are strongly supported (Figure 10).…”
Section: Resultsmentioning
confidence: 93%
“…Recent molecular studies focusing on these different genera have shown that most of the taxa alleged to be common species with wide geographic distributions were actually constituted by complexes of several cryptic or pseudo-cryptic species with relatively restricted allopatric distributions (Datta-Roy et al 2012;Hedges & Conn 2012;Miralles et al 2009, Miralles & Carranza 2010Sindaco et al 2012). These observations led us to investigate herein the molecular differentiation within two Madagascar-endemic species of Trachylepis that are among the most widespread and common Malagasy reptiles, namely, T. elegans (Peters) and T. gravenhorstii (Duméril & Bibron).…”
Section: Introductionmentioning
confidence: 99%
“…Further, they suggest the presence of cryptic species, although further sampling would be required to confirm this possibility. Also, Miralles et al (2009) studying the phylogeny of the Caribbean skinks (Mabuya), a genus with a wide altitudinal distribution, found a new species (Mabuya zuliae) on the lowlands of the Maracaibo lake basin, West of the MA, in the general area where we sampled tegu lizards. On the other hand, Vargas-Ramírez et al (2013) found no molecular differences on populations of the turtle Rhinoclemmys on either side of the Andes but the taxonomy remains unchanged because of the allopatric and parapatric distribution of the genus and the species Rhinoclemmys melanosterna, as well as the caryological and morphological differences.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is evidence that both barriers have affected the genetic structure and/or the distribution of several taxa, including capybaras (Mones, 1991), bats (Romero, 2003), snakes (Schargel, Fuenmayor, Barros, Péfaur, & Navarrete, 2007;Scartozzoni, Trevine, & Germano, 2010), lizards (Miralles et al, 2009;Stephen, Reynoso, Collett, Hasbun, & Breinholt, 2013), turtles (Vargas-Ramírez et al, 2012, Vargas-Ramírez, Carr, & Fritz, 2013 and birds (Pereira & Baker, 2004). Using these conditions, both the Paleogeographic and the Riverine hypothesis can be tested.…”
mentioning
confidence: 99%